2023
DOI: 10.3390/admsci13060146
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Innovation and Export Performance of Hungarian Family and Non-Family Enterprises: Experiences Drawn from Empirical Surveys

Abstract: Family enterprises are considered to be one of the oldest and still dominant forms of business organisations. However, their innovation activity is an emerging area of research, especially in the Central and Eastern European region. The aim of our study is to address this research gap by investigating, with the help of statistical tools, the relationship between the familiness of the firms, their innovation activity, and their export activity on representative samples of Hungarian SMEs in the years 2017, 2020,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…However, in our sample, family firms could not rely on their innovation capabilities to reach higher performance, thus leading to the conclusion that they seem only as innovative as non-family businesses, no better or less. This is similar to the findings of Paunović et al (2023) who also found that family and non-family businesses are equally committed to introducing innovations in their business processes and to Csákné Filep et al (2023) who found no difference between family and non-family firms regarding their innovation performance in their 2017 and 2022 samples.…”
Section: Iv5 Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, in our sample, family firms could not rely on their innovation capabilities to reach higher performance, thus leading to the conclusion that they seem only as innovative as non-family businesses, no better or less. This is similar to the findings of Paunović et al (2023) who also found that family and non-family businesses are equally committed to introducing innovations in their business processes and to Csákné Filep et al (2023) who found no difference between family and non-family firms regarding their innovation performance in their 2017 and 2022 samples.…”
Section: Iv5 Discussionsupporting
confidence: 87%
“…They claimed if family firms were more similar to non-family firms and professionalized, they could reach a higher level of performance and be more competitive. Comparing family and non-family businesses along different corporate measurements has a long history from various research contexts, such as the US , Italy (Culasso et al, 2015), Finland (Kirmanen & Kansikas, 2010;Larimo, 2013) Chile (Martínez et al, 2007) and recently Hungary (Wimmer & Matolay, 2020;Csákné Filep et al, 2023) with mixed results, either family firms outperform non-family businesses, or they indeed have some kind of a disadvantage of family ownership.…”
Section: Iv1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing the innovative activity of family businesses, with the help of statistical tools, the relationship between the family character of companies, their innovative activity and their export activity demonstrate an opportunity that is based on the possibilities of integration and mutual strengthening of innovation and export activities in parallel (Csákné et al, 2023). The It is mentioned that family businesses show resistance to change and that business families seek continuous improvement, and although this generates conflicts, it should be considered as an opportunity, because it is possible to create solid links to build work environments with corporate values (Combs et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…At the academic level, we find a fundamental opportunity that would be the inclusion of FB within economic theory for research in universities. (Johansson et al, 2020), sustained by the human resources of the MZ generation (Kim & Kim, 2022); however, the operational or the academic is insufficient in the digital age and, as real opportunities, there is the creation of ecosystems for co-creation of value, collaborative agreements, open FBs and the linking of family value and business value (Randerson & Estrada-Robles, 2023;Csákné Filep et al, 2023;Lambrechts et al, 2023;De Groote et al, 2023).…”
Section: Factors Characteristics Strengths Challenges and Opportuniti...mentioning
confidence: 99%